2014
DOI: 10.1001/jamaoto.2014.757
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Risk in Children With Cochlear Implants

Abstract: IMPORTANCE Children who receive a cochlear implant (CI) for early severe to profound sensorineural hearing loss may achieve age-appropriate spoken language skills not possible before implantation. Despite these advances, reduced access to auditory experience may have downstream effects on fundamental neurocognitive processes for some children with CIs. OBJECTIVE To determine the relative risk (RR) of clinically significant executive functioning deficits in children with CIs compared with children with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
119
4
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 40 publications
(64 reference statements)
17
119
4
5
Order By: Relevance
“…As with previous findings, a great amount of variability can be found in verbal working memory (ranges from clinical deficits of −2 SD to above average), fluency speed (ranges from clinical deficits of −2 SD to above average), and inhibition concentration (ranges from clinical deficits of −4 SD to above average) performance. For more-stable estimates of the rate of executive functioning deficits based on a larger sample, see Kronenberger, Beer et al (2014) for performance data and Kronenberger, Colson et al (2014) for questionnaire-based data on relative risk. After controlling for nonverbal intelligence, the development of early expressive language, as indexed by vocabulary size obtained from the CDI, was found to be significantly associated with long-term performance-based, and questionnairebased measures of neurocognitive skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with previous findings, a great amount of variability can be found in verbal working memory (ranges from clinical deficits of −2 SD to above average), fluency speed (ranges from clinical deficits of −2 SD to above average), and inhibition concentration (ranges from clinical deficits of −4 SD to above average) performance. For more-stable estimates of the rate of executive functioning deficits based on a larger sample, see Kronenberger, Beer et al (2014) for performance data and Kronenberger, Colson et al (2014) for questionnaire-based data on relative risk. After controlling for nonverbal intelligence, the development of early expressive language, as indexed by vocabulary size obtained from the CDI, was found to be significantly associated with long-term performance-based, and questionnairebased measures of neurocognitive skills.…”
Section: Discussionmentioning
confidence: 99%
“…Parent-teacher interrater reliability is modest (r = 0.21-0.34 for eight of the 11 LEAF subscales). Additionally, construct validity between corresponding subscales on the LEAF and other behavior checklists is also strong (see Kronenberger, Beer et al, 2014, for comparisons of executive functioning skills in CI users and in NH children using the LEAF and another behavior checklist).…”
Section: Long-term Neurocognitive Questionnaire-based Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…Research involving deaf individuals with and without CIs has indicated them frequently to report or demonstrate greater EF difficulties relative to hearing peers (e.g., Hauser, Lukomski, & Hillman, 2008;Hintermair, 2013;Kronenberger, Beer, Castellanos, Pisoni, & Miyamoto, 2014;Pisoni, Conway, Kronenberger, Henning, & Anaya, 2010). Samples of deaf children, adolescents, and young adults have been found to have difficulties (relative to hearing peers) in specific EF domains such as verbal working memory (Hintermair, 2013;Marschark, Sarchet, & Trani, 2016;Kronenberger, Beer et al, 2014;Kronenberger, Pisoni, Henning, & Colson, 2013), controlled fluency speed (controlled attention under time pressure; Kronenberger et al, 2013), inhibition versus impulsivity (Figueras, Edwards, & Langdon, 2008;Kronenberger et al, 2013), and concept formation (Castellanos et al, 2015;Figueras et al, 2008;Kronenberger, Beer et al, 2014). Other EF areas such as flexibility/shifting (Figueras et al, 2008;Hintermair, 2013;Kronenberger, Beer et al, 2014) and emotional control (Hintermair, 2013;Kronenberger, Beer et al, 2014) may be affected, although there is some inconsistency in findings for these domains particularly at young ages (Kronenberger, Beer et al, 2014).…”
Section: Executive Function Language and Social Functioning Among Dmentioning
confidence: 99%
“…Samples of deaf children, adolescents, and young adults have been found to have difficulties (relative to hearing peers) in specific EF domains such as verbal working memory (Hintermair, 2013;Marschark, Sarchet, & Trani, 2016;Kronenberger, Beer et al, 2014;Kronenberger, Pisoni, Henning, & Colson, 2013), controlled fluency speed (controlled attention under time pressure; Kronenberger et al, 2013), inhibition versus impulsivity (Figueras, Edwards, & Langdon, 2008;Kronenberger et al, 2013), and concept formation (Castellanos et al, 2015;Figueras et al, 2008;Kronenberger, Beer et al, 2014). Other EF areas such as flexibility/shifting (Figueras et al, 2008;Hintermair, 2013;Kronenberger, Beer et al, 2014) and emotional control (Hintermair, 2013;Kronenberger, Beer et al, 2014) may be affected, although there is some inconsistency in findings for these domains particularly at young ages (Kronenberger, Beer et al, 2014). Differences between deaf and hearing samples typically are not found on visuospatial working memory tasks (Marschark, Sarchet et al, 2016;Kronenberger et al, 2013) or visual-organizational EF tasks (Kronenberger, Beer et al, 2014;Kronenberger et al, 2013).…”
Section: Executive Function Language and Social Functioning Among Dmentioning
confidence: 99%